Designing an Enterprise Architecture Using TOGAF ADM Framework (Case Study: PT. Indorama) - Feby Janiar Husein; Melissa Indah Fianty (Universitas Multimedia Nusantara, 2023)
This research aims to create an information technology architecture that will automate the company's business processes that focus on customer relationship management systems using a case study from PT Indorama. Enterprise IT Architecture must complement the vision and organizational goals and match the needs of business processes. As a result, creating IT blueprints is critical for businesses to make the future development of information systems easier. TOGAF ADM was used to create the IT architecture for this investigation. To integrate current system applications, Customer Relationship Management (CRM) based applications are used to complete various business tasks that are not currently enabled by the current application system. This research results in the design of an IT architecture to support the company's strategic plans through business process automation and answer predetermined challenges. Keywords— Enterprise Architecture, Customer Relationship Management, TOGAF ADM